A COMPARISON ON THE LEVEL OF KNOWLEDGE AMONG RURAL AND URBAN WOMEN IN COLOMBO DISTRICT REGARDING BREAST CANCER - De Zoysa, M.I.M.; Janaki, S.S.A.B.; Hettiarachchi, D.P. (My University, 2012)
Early detection of a breast cancer enables to intervene at appropriate the time and for a better outcome. Here, the patient's role becomes invaluable and the awareness about breast cancer in the society has a direct impact on the rate of diagnosing early breast cancers. The study was conducted to assess the knowledge among women about breast cancer and its management and to find out the impact of social status on the existing level of knowledge.